Parametric Study on Exergy and NOx Metrics of Turbofan Engine Under Different Design Variables - Aygun, Hakan; Sheikhi, Mohammad Rauf; Kirmizi, Mehmet (Asme, 2022)
Examining the effects of design variables on performance and emission parameters for gas turbine engines is of high importance. In this study, the effects of by-pass ratio (BPR) and turbine inlet temperature (TIT) of turbofan engine on energy, exergy, and exhaust emissions are parametrically analyzed at 0.85 Ma and altitude of 11 km. Moreover, cruise NOx emission is quantified by Boeing Fuel Flow Method 2 (BFFM2) and DLR methods. As a novelty, specific NOx production (SNP) is first quantified for PW4000 engine. In this study, parametric cycle equations regarding turbofan engine are encoded so as to compute performance and emission metrics. According to energy analysis, specific fuel consumption (SFC) of the turbofan averagely changed from 19.82 to 18.64 g/kNs due to rising BPR whereas it increases from 18.62 to 19.93 g/kNs owing to rising TIT. Furthermore, exergy efficiency of turbofan rises from 27.67% to 29.42% due to rising BPR whereas it decreases from 29.46% to 27.65% owing to rising TIT. As for NOx emission results, the higher BPR leads to the lowering of the SNP index of the turbofan from 0.46 to 0.375 g/kNs while the higher TIT yields to the increase of the SNP index from 0.377 to 0.455 g/kNs. According to the findings of this study, the decision mechanism could be improved to find out optimum design variables in terms of eco-friendly aircraft activities.
Keywords: turbofan; NOx emission; exergy; exergo-sustainability; efficiency; air emissions from fossil fuel combustion; energy conversion; systems; energy systems analysis